Cybertroops: Contestation and Polarization in The Perspective of Critical Discourse Analysis - Khoirun Nisa Aulia Sukmani; Taufik Setyadi Aras (LEGAL BRIEF, 2024)
The political year is approaching; every five years, Indonesia faces a contestation of democracy and political games. Cybertroops act as a volunteer force in influencing public opinion on certain topics, creating polarization that attracts the attention of the government in defending against opinions that damage and endanger Indonesia’s integration. How is it viewed? This research uses social media ethnography to observe the landscape of cybertroops and virtual police in their respective domains. Critical Discourse Analysis is used to see how cybertroops to work in cultivating public opinion, while virtual police monitor and minimize the growth of public opinion polarization.